2019
DOI: 10.1002/etc.4514
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen and Its Phototransformation Products: Persistence and Ecotoxicity to Toad Tadpoles (Anaxyrus terrestris), Individually and in Mixtures

Abstract: Although pharmaceutical pollution is a global environmental concern, much remains unknown about the transformation of pharmaceuticals in the wild and their effects on wildlife. In the environment, pharmaceuticals typically transform to some extent into different, structurally related compounds. Pharmaceutical transformation products resulting from exposure to sunlight (i.e., ultraviolet radiation) in surface waters are of particular concern; these products can be more hydrophobic, persistent, and toxic than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…In a previous study on UV photodegradation of Naproxen by Cory et al., only PP2 and PP3 were detected though the experimental conditions were quite similar to those used in the present work. 20 Like in the present study, both photo-transformation products of Naproxen were found to be more stable than Naproxen itself when exposed to simulated sunlight; their toxicity was investigated towards toad tadpoles and they have been shown to be much more toxic than the parent molecule.…”
Section: Resultssupporting
confidence: 57%
“…In a previous study on UV photodegradation of Naproxen by Cory et al., only PP2 and PP3 were detected though the experimental conditions were quite similar to those used in the present work. 20 Like in the present study, both photo-transformation products of Naproxen were found to be more stable than Naproxen itself when exposed to simulated sunlight; their toxicity was investigated towards toad tadpoles and they have been shown to be much more toxic than the parent molecule.…”
Section: Resultssupporting
confidence: 57%
“…Studies on the occurrence and fate of TPs show that, in addition to the API, many environmental organisms are exposed to TPs (e.g. [97][98][99]).…”
Section: Persistence Assessmentmentioning
confidence: 99%
“…Most often and in relatively low concentrations (from ng/L to µg/L),those are massively consumed antibiotics, anti-inflammatory drugs (NSAIDs), hormones, antispasmodics, antihypertensives, anticancer agents, anticonvulsants and antidepressants;and also statins and antidiabetic drugs increasingly usedowing to the spread of sedentary lifestyles associated with urbanization [1]. As reported in a number of studies,pharmaceutical pollutants with pronounced biological activity and high chemical resistance, have negative impacts on invertebrates [2][3][4], vertebrates [5,6], plants [7,8], and also disrupt the structure and functioning of ecosystems [9,10]. However, the nature of such impacts of pharmaceutical compounds on natural microorganisms, which represent a native system of "primary response" to xenobiotic load in open ecosystems, is still insufficiently studied.…”
Section: Introductionmentioning
confidence: 99%